Simplified Equations to Find the Relationship Between Soil and Structure Displacements for Rectangular Single Column and Footing on Dry Voidless Cohesionless Soil Due to Vertical Loads - Fawzi Abu Al-Adas; Abdul Razzaq Touqan (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
Usually, structural designers are assuming the soil as rigid object when they design small to intermediate structures, or assuming the settlement of soil to be always within the acceptable range. However, the engineering practice shows that high percentage of cracks and failures in structures are related to soil settlement reasons, non-uniform soil settlement for example. Geotechnical engineers developed many methods to calculate the settlement of soil, but the majority of these methods are geotechnical engineering oriented, and standard structural engineer may struggle using them. Therefore, because of the importance of finding the approximate soil settlement in many cas-es during the design process or during the implementation of the structure, this study gives simple equations that can predict the soil settlement with acceptable accuracy, by creating a relationship between the soil settlement and the displacement of the structure. The targeted equation will allow us to find the soil settlement from knowing the approximate displacement of the structure. Such an equation gives a conceptual value to be used in 3D analysis of structures using computer programs like SAP2000 and ETABS. The targeted structure in this study is a simple one rectangular column and footing structure